2016
DOI: 10.1093/toxsci/kfw157
|View full text |Cite
|
Sign up to set email alerts
|

MC1568 Inhibits Thimerosal-Induced Apoptotic Cell Death by Preventing HDAC4 Up-Regulation in Neuronal Cells and in Rat Prefrontal Cortex

Abstract: Ethylmercury thiosalicylate (thimerosal) is an organic mercury-based compound commonly used as an antimicrobial preservative that has been found to be neurotoxic. In contrast, histone deacetylases (HDACs) inhibition has been found to be neuroprotective against several environmental contaminants, such as polychlorinated biphenyls, di-2-ethylhexyl phthalate, and methylmercury. The aim of this study was to investigate the effect of HDAC inhibition on thimerosal-induced neurotoxicity in neuroblastoma cells and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…In fact, MeHg exposure increased HDAC4 gene and protein expression causing also in the nucleus an increase of its binding to the BDNF gene promoter IV sequence with consequent mRNA and protein reduction of this neuroprotective factor. These results are in accordance with recent in vivo studies demonstrating that intramuscular injection of the organomercury compound thimerosal induces neuronal cell death by increasing HDAC4 expression in rat prefrontal cortex (Guida et al, 2015b, 2016), and that in cortical neurons HDAC4 knockdown improves neuronal survival after oxygen glucose deprivation (OGD, Yuan et al, 2016). Furthermore, we found that of the three main branches of the MAPK cascade (ERK, p38, and JNK), only p38 was involved in regulating HDAC4 gene expression in cells exposed to MeHg.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In fact, MeHg exposure increased HDAC4 gene and protein expression causing also in the nucleus an increase of its binding to the BDNF gene promoter IV sequence with consequent mRNA and protein reduction of this neuroprotective factor. These results are in accordance with recent in vivo studies demonstrating that intramuscular injection of the organomercury compound thimerosal induces neuronal cell death by increasing HDAC4 expression in rat prefrontal cortex (Guida et al, 2015b, 2016), and that in cortical neurons HDAC4 knockdown improves neuronal survival after oxygen glucose deprivation (OGD, Yuan et al, 2016). Furthermore, we found that of the three main branches of the MAPK cascade (ERK, p38, and JNK), only p38 was involved in regulating HDAC4 gene expression in cells exposed to MeHg.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, siRNAs against Sp1 reduced Sp1 protein expression respectively of 80 and 68% in SH-SY5Y cells and rat cortical neurons, as already published (Formisano et al, 2015b). Whereas, siRNAs against HDAC4 reduced HDAC4 protein expression respectively of 75 and 71% in SH-SY5Y cells and rat cortical neurons, as already published (Guida et al, 2016). They were also transfected with siRNAs against human and rat Sp4 (siSp4; SI04333588) at 20 nM, both purchased from Quiagen.…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations